PERAN KEHUMASAN DALAM MENINGKATKAN PELAYANAN PUBLIK BERBASIS CETAK BIRU DI UNIVERSITAS NEGERI MAKASSAR - Basri, Syamsurijal (Pascasarjana Universitas Negeri Makassar, 2018)
This study examines the role of public relation Â in improving Public Services-based blueprint in Makassar State University. This study aims to investigate the role of public relations in improving public services based on the blueprint of the State University of Makassar. This study employed a descriptive quantitative research method. The data were collected from civil servants, journalists and students. In this study, the author utilized a purposive sampling technique with 60 respondents involved in the survey. The participants consisted of 20 civil servants, 20 journalists, and 20 students. The data analysis technique employed descriptive statistic al analysis using presentations. The results showed the role of public relations in improving public services based on blueprints. The indicators of the capacity of public relations were rated B (Good) with a percentage of 56%. This shows that the public relations were able to manage information, data, documentation and publications. However, it still needs to improve the public relation personnel in accordance with the background of public relations and resource development in order to manage public relations. The indicators of mainstream of public information rated B (good) with a percentage of 72%. This suggests that the availability of access to information on public relations is good and the public can access information according to their needs, indicators for reinforcing institutional public relations, its role assessed as fair with a percentage of 48%. The results showed that the importance of managing public relations in order to create better public services.